2017
DOI: 10.7150/ijms.17469
|View full text |Cite
|
Sign up to set email alerts
|

Changes of articular cartilage and subchondral bone after extracorporeal shockwave therapy in osteoarthritis of the knee

Abstract: We assessed the pathological changes of articular cartilage and subchondral bone on different locations of the knee after extracorporeal shockwave therapy (ESWT) in early osteoarthritis (OA). Rat knees under OA model by anterior cruciate ligament transaction (ACLT) and medial meniscectomy (MM) to induce OA changes. Among ESWT groups, ESWT were applied to medial (M) femur (F) and tibia (T) condyles was better than medial tibia condyle, medial femur condyle as well as medial and lateral (L) tibia condyles in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 32 publications
3
61
0
1
Order By: Relevance
“…Eighteen 12‐week‐old male Sprague Dawley rats‐(280–320 g) were used in the study. First, 12 rats were randomly picked out and received bilateral anterior cruciate ligament transection and destabilization of the medial meniscus according to the previous study (C. J. Wang, Cheng, Huang, et al, ), whereas the remaining six rats and 12 legs received sham arthrotomy. The 12 with surgeries were randomly divided into two groups, namely, PBS group (PBS) and CM group (CM), and the six with sham surgeries were normal control group (normal).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen 12‐week‐old male Sprague Dawley rats‐(280–320 g) were used in the study. First, 12 rats were randomly picked out and received bilateral anterior cruciate ligament transection and destabilization of the medial meniscus according to the previous study (C. J. Wang, Cheng, Huang, et al, ), whereas the remaining six rats and 12 legs received sham arthrotomy. The 12 with surgeries were randomly divided into two groups, namely, PBS group (PBS) and CM group (CM), and the six with sham surgeries were normal control group (normal).…”
Section: Methodsmentioning
confidence: 99%
“…The animals were euthanized by CO 2 overdose at 8 weeks postoperatively, and the knee specimens were collected and analysed. The gross morphology of articular cartilage of femurs and tibias was inspected under a magnification scope (Carl Zeiss, Oberkochen, Germany) and scored following the protocol of a previous study (C. J. Wang, Cheng, Chou, et al, ) by a blinded observer. The specimens were fixed in 10% formalin for 72 hr and decalcified in EDTA solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that ESWT can generate radial or focused pressure waves which bring energy and propagate through tissue [62]. This physical force could stimulate biological effects in a treated area, and the biochemical mechanism of ESWT in OA might be associated with neovascularization, osteogenesis, and chondrogenesis [63][64][65]. In recent studies, ESWT might lead to upregulation of angiogenic growth factors including endothelial nitric oxide synthase (eNOS) and vessel endothelial growth factor (VEGF), which benefit to neovascularization [66].…”
Section: Comparison Of Functional Improvementmentioning
confidence: 99%
“…Традиционно применяют УВТ при остеоартритах и остеоартрозах коленного сустава [7,19,20,21], остеоартрозах суставов кисти, псевдоартроза, ложного сустава и т.д. [5,18,19]. Доказано влияние УВТ на эластический компонент связок и сухожилий, увеличение подвижности и уменьшение периода скованности в мелких суставах, снижение эксплицированности болевого синдрома [5].…”
Section: Discussionunclassified